COMPARISON OF FREE ANDROGEN INDEX IN POLYCYSTIC OVARY SYNDROME AND NON-POLYCYSTIC OVARY SYNDROME INFERTILE PATIENTS - Khattak, Madiha; Usman, Robina; Sultana, Nuzhat; Khattak, Almas (Journal of Ayub Medical College Abbottabad, 2021)
Background: One of the leading causes of infertility in child bearing age females is polycystic ovary syndrome. It is characterized by altered hormonal profile causing androgen excess and insulin resistance which eventually leads to decreased ovulation rate. Methods: This was a cross-sectional study that included 40 Polycystic ovary syndrome (PCOS) patients and 40 infertility patients that did not have polycystic ovary syndrome determined by sonography and clinical features through quota sampling technique. Serum Total Testosterone and Sex Hormone Binding Globulin Levels were assayed. Using these two parameters, Free Androgen Index was calculated. Body Mass Index and central obesity was also determined. Results: Total Testosterone, Free Androgen Index and Body Mass Index were raised in PCOS group as indicated by p-value <0.05. Hirsutism was present in PCOS group (p-value <0.05). Sex Hormone Binding Globulin Levels were decreased in PCOS patients (p-value <0.05) but were within the lower half of normal range. Conclusion: Levels of Sex Hormone Binding Globulin were decreased in PCOS cases and Free Androgen Index can help in better determining hyperandrogenaemia than total testosterone alone.